Land cover mapping of the Mekong Delta with sentinel-1 synthetic aperture radar - Ngo, Duc Khanh (2024)
Synthetic aperture radar (SAR) has great potential for land cover/land use (LCLU) mapping, especially in tropical regions, where frequent cloud cover obstructs optical remote sensing. The use of SAR data derived mapping results plays crucial role in urban and suburban extents characterizations, urban services, rice crop distribution delineation, and land use changes detection. As the Mekong Delta is a significant location ecologically, economically, and socially, food security, forest conservation, natural resource management, and urbanization are a matter of great concern. Urban expansion and conversion wetland areas to aquaculture have impacts on natural forest and coastal ecosystems in the Mekong Delta. Therefore, the use of latest Sentinel-1 C-band SAR data characterizing LCLU including urban expansion, aquaculture development, and productive land and unproductive lands is essential for natural resource management and land use planning.